Soccer injuries and `Training right` to return to play - Efe, E. (2018)
The following questions and topics concerning soccer injuries and `Training right` to return to playare answered: "When can I play again?" What and how much load can be put on the injured player? What is the right acute:chronic workload ratio? How do I measure load? Managing (and building) load - the "Goldilocks" approach. Return to sport. Maintenance of high training loads.